2014
DOI: 10.6023/a14080596
|View full text |Cite
|
Sign up to set email alerts
|

Doxorubicin-Loaded Silk Fibroin Nanospheres

Abstract: Silk protein from silkworms or spiders is a very promising biomaterial due to its renewability, nontoxicity, biocompatibility and biodegradability, so it has been widely used in biomedical and pharmaceutical fields. In this article, we report our attempt to use regenerated Bombyx mori silkworm silk fibroin (RSF) as a drug-carrier to encapsulate anti-cancer drug doxorubicin (DOX). Firstly, the pristine RSF nanospheres are prepared by using a facile and clean method developed in this laboratory previously based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
1
6
0
1
Order By: Relevance
“…The loading efficiency was comparable or significantly higher than previous silk particle systems. 43,47 The total amount of loaded drug Several studies have confirmed that the DOX loading capacity of silk particles was mainly dependent on negative charge and hydrophobic properties. 5,31 Thus, it is reasonable that the SNPs-F particles had a lower loading percentage at lower ratios.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…The loading efficiency was comparable or significantly higher than previous silk particle systems. 43,47 The total amount of loaded drug Several studies have confirmed that the DOX loading capacity of silk particles was mainly dependent on negative charge and hydrophobic properties. 5,31 Thus, it is reasonable that the SNPs-F particles had a lower loading percentage at lower ratios.…”
Section: Resultssupporting
confidence: 79%
“…Compared to that of SNPs-A, lower drug levels were absorbed on the SNPs-F particles at lower DOX/silk ratios, and then became similar when the ratio was in the range of 0.3–0.6. The loading efficiency was comparable or significantly higher than previous silk particle systems. , The total amount of loaded drug increased and remained constant at about 50 μg after more than 200 μg of DOX was added in aqueous solutions containing 500 μg of silk nanoparticles, suggesting saturation. Several studies have confirmed that the DOX loading capacity of silk particles was mainly dependent on negative charge and hydrophobic properties. , Thus, it is reasonable that the SNPs-F particles had a lower loading percentage at lower ratios.…”
Section: Results and Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Direct comparisons with BUXZEZ (Yang et al, 1983) are difficult because of the disorder around the allyl group while the remaining compounds have other significant intermolecular interactions such as hydrogen bonds formed to bromide by a water molecule (CEXLOG, GINHAN) or from a carboxylic acid (YOYWEO). Similar interactions to compound 1 can be seen where chloride is the halide anion: BIDBIZ (Shao et al, 1982) shows hydrogen bonds from the benzylurotropinium cation to the chloride anion, accounting for 12.2% of the interaction surface.…”
Section: Database Surveymentioning
confidence: 99%
“…As far as we know, there have been a few nanocarriers that have such high drug-loading efficiency. [19][20][21][22] The oMCNs showed a significant advantage as containers for DOX.…”
mentioning
confidence: 99%